1992
DOI: 10.1063/1.860355
|View full text |Cite
|
Sign up to set email alerts
|

Nonlinear studies of m=1 modes in high-temperature plasmas

Abstract: No.nlinear evolution of the m = 1 mode is examined in high-temperature plasmas where the mode is in the semi-col.lisional or collisJ,onless regime.. Unlike 'the resistive m = t mode, both the semi-collisional mode, with a very weak resistivity dependence, and the collisionless mode, driven by finite electron inertia, can be robustly unstable in today's large tokamaks. And un l,ike the finite-zX'(m _>2) tearing modes, the nonlinear evolution of which is collisional, both the semi-collisional and collisionless m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

13
132
0

Year Published

2001
2001
2013
2013

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 170 publications
(145 citation statements)
references
References 13 publications
13
132
0
Order By: Relevance
“…[18]. In general we use a hyper-viscosity coefficient equal to that of hyper-resistivity, but we have verified the independence of the reconnection rate by varying the two coefficients also separately.…”
Section: Iva the Harris Sheetmentioning
confidence: 79%
See 1 more Smart Citation
“…[18]. In general we use a hyper-viscosity coefficient equal to that of hyper-resistivity, but we have verified the independence of the reconnection rate by varying the two coefficients also separately.…”
Section: Iva the Harris Sheetmentioning
confidence: 79%
“…15 * ≤ t , the early growth rate of the perturbation agrees also well with the prediction of classical [14] linear tearing mode theory, taking the value of of the Harris sheet for vanishing island width, although the requirements for its validity ( Tables 1 and 2 give some quantitative results of our Harris-sheet simulations, and among others, also the ratio of the current sheet width (taken at half the maximum value of ) in y Introduction of electron pressure effects has been found in Refs. [9,18] to allow, like the Hall effect, for a decoupling of plasma flows and field lines over a spatial scale of the order s ρ . This can be seen from the fact that the term…”
Section: Iva the Harris Sheetmentioning
confidence: 99%
“…For example, in 1964 Petschek proposed a fast reconnection model involving shock formation near the reconnection layer, which predicted Unforv r \ v A / ln S. tunately, subsequent numerical (Biskamp 1986) and theoretical (Kulsrud 2000) study has indicated that PetschekÏs model is internally inconsistent. While research on fast, laminar reconnection continues today (i.e., Aydemir 1992 ;Wang & Bhattacharjee 1993 ;Kleva, Drake, & Waelbroeck 1995 ;Shay et al 1999) in the context of two-Ñuid models, the failure of the Petschek scenario has sparked increased interest in turbulent reconnection (Matthaeus & Lamkin 1986) in which turbulent transport coefficients (which can be large for large Reynolds number) act as e †ective dissipation coefficients, and so are thought to facilitate fast reconnection (i.e., Diamond et al 1984 ;Strauss 1988). Interest in turbulent reconnection has also been stimulated by the fact that many instances of reconnection occur in systems where turbulence is ubiquitous, i.e., coronal heating of turbulent accretion disks, the dynamo in the sunÏs convection zone, and turbulent tokamak plasmas during disruptions.…”
Section: Introductionmentioning
confidence: 99%
“…To support such an electric field, and hence reconnection, the electron pressure is important for the electron momentum balance. Standard fluid models and simulation schemes often rely on isothermal or adiabatic equations of state for a fluid closure [4][5][6]. Meanwhile, measurements taken by the Wind spacecraft in a reconnecting current sheet in the Earth's magnetotail show that the electron phase space density is highly anisotropic, with T k ) T ?…”
mentioning
confidence: 99%